Ethnographic analogy and the reconstruction of early Khoekhoe society - Barnard, A. (Southern African Humanities, 2021)
Recent thinking sees the earliest Khoekhoe as a kind of San with livestock. Eighteenth-century travellers sometimes seem to have seen San as a kind of Khoekhoe without livestock. Classic ethnographic sources saw Khoekhoe and San as related peoples, one with livestock and one without. Some in recent years have suggested that Khoekhoe and San are unstable ethnicities, shifting back and forth with the acquisition and loss of livestock. Is there a correct view? This paper attempts to answer that question. One theme of the paper is the idea that the acquisition of livestock by twentieth-century Khoe-speaking hunter-gatherers might serve as an analogy for deciphering similar processess among early Khoekhoe. The shifting lifestyles from hunter to herder and back again in the Cape are now well documented in the historical and archaeological records. Similar processes have been observed by ethnographers in the Kalahari since the 1970s. Another theme is the more theoretical concern of Khoekhoe and San social structure and social ideology.